Localization of MRNA storage complexes in Plasmodium berghei throughout the life cycle - Pereira, Marcelo Luís Monteiro, 1987 (2012)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2011